Predictive Modeling and Big Data Analytics ‎for Optimizing Refractory Material ‎Composition and Performance Evaluation - Mariadas, A. Emmanuel Peo; Radha , R.; Jenifer , P. Immaculate Rexi; Kumar, S. Praveen; Garladinne , Ravikanth; Dhanalakshmi , P. (International Journal of Basic and Applied Sciences, 2025)
Refractory materials are essential for high-temperature industrial processes, where precise composition is critical to ensuring optimal per-‎formance. However, variability in raw materials and operating conditions poses significant challenges in maintaining consistent quality. ‎Traditional trial-and-error optimization methods are inefficient and fail to leverage the vast amounts of data generated in modern manufactur-‎ing, leading to inconsistent material performance, increased costs, and prolonged development cycles. To overcome these limitations, we ‎propose the Refractory Materials using Big Data Analytics (RM-BDA) framework, which integrates AI-driven predictive modeling with ‎advanced data analytics. RM-BDA leverages both historical and real-time data—including raw material characteristics, processing parame-‎ters, and performance metrics—to accurately predict optimal formulations and improve material performance. Using machine learning algo-‎rithms and robust data processing techniques, RM-BDA enhances prediction accuracy and accelerates formulation optimization. This allows ‎manufacturers to proactively adjust compositions and operational settings to meet targeted performance requirements, reducing waste and ‎improving efficiency. Additionally, the system dynamically responds to fluctuations in material inputs and process conditions, offering real-‎time optimization recommendations. Results demonstrate that RM-BDA significantly improves the accuracy of performance predictions, ‎reduces production costs, and enhances the consistency and quality of refractory materials. By replacing inefficient traditional methods with ‎a data-driven approach, this framework marks a substantial advancement in the field of refractory material development and optimization‎.